2015
DOI: 10.3233/wor-141882
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort assessment of a surgical room through computational fluid dynamics using local PMV index

Abstract: The clothing used by both classes, as well as the ventilation conditions, should be revised accordingly to the amount of persons in the room and the type of activity performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The USB data logger was used to collect relative humidity data, the weather station was used to determine the air velocity and temperature, as well as the radiant temperature, and, finally, the anemometer allows to measure velocity accurately, reliably, and quickly [10]- [12]. III.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The USB data logger was used to collect relative humidity data, the weather station was used to determine the air velocity and temperature, as well as the radiant temperature, and, finally, the anemometer allows to measure velocity accurately, reliably, and quickly [10]- [12]. III.…”
Section: Case Studymentioning
confidence: 99%
“…To determine thermal comfort it uses An index, Predicted Mean Vote (PMV), which is an index that predicts the average thermal sensation vote of a large group of people on a 7-point 2022 17 th Iberian Conference on Information Systems and Technologies (CISTI) 22 -25 June 2022, Madrid, Spain ISBN: 978-989-33-3436-2 scale, based on the thermal balance of the human body [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Over the 50 years after the publication of Fanger's original research, this study found 24 studies that specifically applied PMV in hospital environments: [16][17][18]20,21,45,47,48,50,51,54,56,57,59,61,64,66,67,69,71,75,77,78,84]. Considering these 24 studies, 12 of them compared the real thermal sensation vote (TSV), which is the subjective vote obtained through a specific questionnaire, and the calculated PMV.…”
Section: Rq2: Considering Studies Of Thermal Comfort In Hospital Envi...mentioning
confidence: 99%
“…The ability to deal with complex flows within building environments has made CFD an important tool in improving building health and safety, testing energy efficient designs, applying required environment conditions and at the end, to ensure thermal comfort for the occupants. Their accuracy requires three dimensional studies including the unsteady modelling of turbulence, convection, radiation, species and buoyancy [10].…”
Section: Introductionmentioning
confidence: 99%